Revisiting CPSF30-mediated alternative polyadenylation in Arabidopsis thaliana - Guijie Hao; Lichun Zhou; Huazhen Liu; Pradeep Kachroo; Arthur G. Hunt (PLoS ONE, 2025)
Alternative polyadenylation (APA) is an important contributor to the regulation of gene expression in plants. One subunit of the complex that cleaves and polyadenylates mRNAs in the nucleus, CPSF30 (for the 30 kD subunit of the mammalian Cleavage and Polyadenylation Specificity Factor), has been implicated in a wide-ranging network of regulatory events. CPSF30 plays roles in root development, flowering time, and response to biotic and abiotic stresses. CPSF30 also is a conduit that links cellular signaling and RNA modification with alternative RNA processing events and transcriptional dynamics. While much is known about CPSF30 and its roles in plants, questions remain regarding the connections between CPSF30-mediated APA and the downstream events that lead to specific phenotypic outcomes. To address these, we conducted a detailed analysis of poly(A) site usage in the CPSF30 mutant. Our results corroborate earlier reports that link CPSF30 with a distinctive cis element (AAUAAA) that is present 10-30 nts upstream of some, but not all, plant pre-mRNAs. Interestingly, our results reveal a distinctive shift in poly(A) site in mutants deficient in CPSF30, resulting in cleavage and polyadenylation at the location of motifs similar to AAUAAA. Importantly, CPSF30-associated APA had at best a small impact on mRNA functionality. These results necessitate the formulation of new hypotheses for mechanisms by which CPSF30-mediated APA influences physiological processes.